John Foster Carr papers - Carr, John Foster, 1869-1939.
Letters, chiefly from libraries, universities, and patriotic societies, to Carr concerning his work with the Immigrant Publication Society and its work in the education of immigrants.
Educator, lecturer, and author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Immigrant Publication Society; Immigrants -- Education; Authors; Educators; Lecturers